KINEMATIC AND DYNAMIC ANALYSIS OF THE MECHANISM OF A SCREENING TYPE POTATO AND ONION SORTING MACHINE (Western European Journal of Modern Experiments and Scientific Methods, 2025)
Sorting of potatoes and onions represents a critical technological stage in the production process, where minimizing tuber damage is a key performance criterion. Sorting machines equipped with elastic coatings on working surfaces are widely used to reduce impact-related damage. This study presents a kinematic and dynamic analysis of the drive mechanism in the Tolsma sorting machine, with the objective of evaluating its performance characteristics under real operating conditions in the AGROVER potato cluster (Tashkent region, Republic of Uzbekistan). The methodology focuses on assessing inertial loads that are directly responsible for mechanical damage during the sorting process. The results of graphical analysis of the vertical forces acting on tubers during the screen vibrations of the Tolsma machine indicate that these forces align predominantly with gravity, causing tubers to become lodged in the sieve holes. The limited repulsive force (as indicated by values below the horizontal axis) fails to ensure effective product movement, while the deformation of elastic coatings and the oval shape of tubers contribute to increased risk of bruising and clogging. It is concluded that additional mechanical elements do not sufficiently address productivity loss or tuber injury, as both are primarily driven by inertial forces and suboptimal screen geometry. These findings highlight the need for optimization of machine parameters to enhance sorting efficiency and reduce mechanical damage.